Evaluation of HLA typing content of next-generation sequencing datasets from family trios and individuals of arab ethnicity - Dashti, Mohammed; Malik, Md Zubbair; Nizam, Rasheeba; Jacob, Sindhu; Al-Mulla, Fahd; Thanaraj, Thangavel Alphonse (Frontiers in Genetics, 2024)
HLA typing is a critical tool in both clinical and research applications at the individual and population level. Benchmarking studies indicated HLA-HD as the preferred tool for accuracy and comprehensive HLA allele calling. Advent of next-generation sequencing (NGS) revolutionized genetic analysis by providing high-throughput sequencing data. In this study, we evaluate, using the HLA-HD tool, the HLA typing content of whole exome, whole genome, and HLA-targeted panel sequence data from the consanguineous population of Arab ethnicity underrepresented in prior benchmarking studies. We used sequence data from family trios and individuals, sequenced on one or more of the whole exome, whole genome, and HLA-targeted panel sequencing technologies, to evaluate the performance and resolutions across various HLA genes. We incorporated a comparative quality control analysis, assessing the results obtained from HLA-HD by comparing them with those obtained from HLA-Twin tool, to authenticate the accuracy of the findings. We find that alleles across 29 HLA loci can be successfully and consistently typed from NGS datasets. Clinical-grade whole exome sequencing datasets achieved the highest consistency rate at three-field resolution, followed by targeted HLA panel, research-grade whole exome, and whole genome datasets. The study catalogues HLA typing consistency across NGS datasets for a large array of HLA genes, and highlights assessments regarding feasibility of utilizing available NGS datasets in HLA allele studies.